Comparative Evaluation of Lip Prints Among Indian and Malaysian Students - Nagpal, Bhuvan; Hegde, Usha; Sreeshyla, Huchanahalli Sheshanna; Arun , M (Journal of Indian Academy of Forensic Medicine, 2015)
Cheiloscopy, the study of lip prints is an upcoming tool for the identification of persons. The lip  print of every person is unique and can be used for personal identity. This study was done to compare  and determine the most common lip print pattern among Indian and Malaysian students in both the  genders and to ascertain if the lip prints behold the potential for determination of gender of the individual.  Study was conducted on 60 students (30 each from Indian and Malaysian origin) which included  20 males and 40 females. Lip stick was applied on each individual and the lip-print was obtained on a  bond paper. The lip impression patterns were studied classified and recorded using magnifying lens with  light. Study revealed that Type I pattern was seen in 42.7% for complete lip and 36.6% for central portion  of lip among Indian students and 56.1% for complete lip and 60% for central portion of lip among  Malaysian students. Type I pattern is the most common and there is no statistical difference in both the  genders in lip print pattern among Indian & Malaysian students.
Keywords: Cheiloscopy; Lip prints; Gender determination; Racial; Indians; Malaysians